New pattern of individualized management of chronic diseases: focusing on inflammatory bowel diseases and looking to the future - Guo, Xi; Cai, Liyang; Cao, Yuchen; Liu, Zining; Zhang, Jiexin; Liu, Danni; Jiang, Zhujun; Chen, Yanxia; Fu, Min; Xia, Zhaoxia; Yi, Guoguo (Frontiers in Medicine, 2023)
Non-infectious chronic diseases, especially inflammatory bowel diseases (IBDs), hypertension, and diabetes mellitus, are characterized by a prolonged and multisystemic course, and their incidence increases annually, usually causing serious economic burden and psychological stress for patients. Therefore, these diseases deserve scientific and consistent disease management. In addition, the lack of a comprehensive “early disease clues tracking—personalized treatment system—follow-up” model in hospitals also exacerbates this dilemma. Based on these facts, we propose an individualized prediction management system for IBDs based on chronic diseases, focusing on the established IBDs-related prediction models and summarizing their advantages and disadvantages. We call on researchers to pay attention to the integration of models with clinical practice and the continuous correction of models to achieve truly individualized medical treatment for chronic diseases, thus providing substantial value for the rapid diagnosis and adequate treatment of chronic diseases such as IBDs, which follow the “relapse-remission” disease model, and realizing long-term drug use and precise disease management for patients. The goal is to achieve a new level of chronic disease management by scientifically improving long-term medication, precise disease management, and individualized medical treatment, effectively prolonging the remission period and reducing morbidity and disability rates.